PENGARUH RISIKO SISTEMATIS DAN LIKUIDITAS TERHADAP RETURN SAHAM PADA PT. BANK MUAMALAT INDONESIA TBK DI BURSA EFEK INDONESIA - Mursidah Nurfadillah (Universitas Muhammadiyah Kalimantan Timur, 2018)
This study aims to determine the effect of systemic risk and liquidity partially and simultaneously to return stock at PT. Bank Muamalat Indonesia Tbk in Indonesia Stock Exchange. The data used in this research is financial statements in 2012 through 2016. This study uses the classical assumption test and multiple regression analysis and hypothesis testing by F test (simultaneous test), t test (partial test), the coefficient of multiple determination and correlation analysis with 5% significance level.The results of this study can be seen that the influence of systematic risk and liquidity together have a significant effect on stock returns. Liquidity risk systematically and jointly able to explain the ups and downs of the stock return of 71.7%, while the remaining 28.3% is influenced by other variables outside of this study. In this study, multiple linear regression equation is Y = 0.449 + 0,019X1-0,269X2. The systematic risk of a significant effect on stock returns and have a positive relationship. While liquidity has no significant effect on stock returns and has a negative correlation.